Study of The Phenomena of Surface Discharges and Flashover in Nanocomposite Epoxy Resin under the Influence of Homogeneous Electric Fields - Danikas, M.; Verginadis, D.; Sarathi, R. (Engineering, Technology & Applied Science Research, 2019)
A new class of insulating materials is the class of polymer nanocomposites. In the past twenty-five years, a lot of attention was paid to the various electrical, thermal and mechanical properties of polymer nanocomposite materials. In the present work, epoxy resin samples without and with nanoparticles (0 wt%, 1 wt%, 3 wt%, 5 wt%, and 10 wt%) are investigated regarding the surface discharges and the flashover voltages. Four different water droplet arrangements were used, with eight different water conductivities in order to see the effect of the nanoparticle.